2021
DOI: 10.2217/fca-2020-0117
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Cardiac Resynchronization and Implantable cardioverter/defibrillator Therapy: Medtronic Cobalt and Crome

Abstract: Cardiovascular implantable electronic devices have revolutionized the management of heart failure with reduced ejection fraction. New device generations tend to be launched every few years, with incremental improvements in performance and safety and with an expectation that these will improve patient management and outcomes while remaining cost-effective. As a result, today’s cardiac resynchronization therapy (CRT) and implantable cardioverter defibrillator devices are quite different from the pioneering but o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Therefore, it is necessary to reduce the physical discomfort caused by CIED to patients by reducing the size of the device, reducing the number of unnecessary electric shocks, and extending the battery life of the device. The reason is, the size of the device affects the degree of foreign body intrusion that the patient feels [ 18 ], while unnecessary electric shocks can cause anxiety and pain, and even lead to patients giving up using their CIEDs [ 31 ]. Extended battery life can reduce the number of battery replacements, the risk of infection and device damage or failure, and treatment costs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it is necessary to reduce the physical discomfort caused by CIED to patients by reducing the size of the device, reducing the number of unnecessary electric shocks, and extending the battery life of the device. The reason is, the size of the device affects the degree of foreign body intrusion that the patient feels [ 18 ], while unnecessary electric shocks can cause anxiety and pain, and even lead to patients giving up using their CIEDs [ 31 ]. Extended battery life can reduce the number of battery replacements, the risk of infection and device damage or failure, and treatment costs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason is, the size of the device affects the degree of foreign body intrusion that the patient feels [ 18 ], while unnecessary electric shocks can cause anxiety and pain, and even lead to patients giving up using their CIEDs [ 31 ]. Extended battery life can reduce the number of battery replacements, the risk of infection and device damage or failure, and treatment costs [ 31 ]. Regarding how to improve the patient’s acceptance of the device size, previous studies have shown that it can be achieved by optimizing the design so that the skin pressure is evenly distributed on the surface [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] The implantable cardiac pacemaker, defibrillator, and resynchronization devices enabled by new battery technologies revolutionized cardiac health care for patients, providing a treatment for heart disease and sudden cardiac death due to ventricular fibrillation. 5,6 Small, implantable battery-powered pumps are used for controlled delivery of pain medication directly to the spinal cord through intrathecal drug delivery devices (pain pumps) for patients with chronic pain conditions. 7 The impact of battery-powered implantable devices on human health is invaluable.While the power demands, size, capacity, and configuration of the batteries vary based on the type of device and the therapy, there are common requirements for implantable batteries that aid human health.…”
mentioning
confidence: 99%